Complementing SOLAS damage ship stability framework with a probabilistic description for the extent of collision damage below the waterline. (15th August 2019) - Bulian, Gabriele; Cardinale, Mike; Francescutto, Alberto; Zaraphonitis, George
Abstract: SOLAS probabilistic damage stability regulations assess the ship safety level through the attained subdivision index, which is a probabilistic measure of ship survivability combining, in principle, the probability of flooding of (groups of) compartments and the corresponding conditional survivability (the s-factor). However, the present SOLAS framework does not embed a probabilistic model for the extent of collision damage below the waterline. A "worst-case approach" is therefore used for the s-factor when there are horizontal subdivision boundaries below the waterline. This leads to a systematic underestimation of the ship survivability in presence of horizontal subdivision boundaries below the waterline, and it prevents an effective assessment of the impact of such boundaries. To make a step forward, the paper presents a probabilistic model for the extent of damage below the waterline, derived from statistical analysis of collision accidents data. From this model, a "u-factor" is defined, and it is described how the "u-factor" could be straightforwardly embedded in the SOLAS framework, in combination with "p-factor", "r-factor" and "v-factor", to consistently account for horizontal subdivision boundaries below the waterline, thus avoiding the need for using the "worst-case approach". An example application is reported to quantitatively assess the effect of the "u-factor". Highlights: Collision accidents data are analysed. A simplified probabilistic model is developed for the extent of collision damage below the waterline. A "u-factor" is defined, which can be straightforwardly embedded in the SOLAS probabilistic damage ship stability framework. The "u-factor" allows to avoid the "worst-case approach" when horizontal subdivision boundaries are below the waterline. The effect of the "u-factor" is assessed through an example application.